ANALISIS WACANA KRITIS PADA LAPORAN UTAMA â€œGADUH JENDERAL GATOTâ€ DI MAJALAH TEMPO - Permada, Arie; Martono, Martono; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrack This study provides a view of how the national press Tempo magazine presented the case statement of the import of 5,000 guns and illegal political maneuvering Commander TNI General Gatot Nurmantyo in the rubric of the main report edition 2â€“8 October 2017. This study uses a qualitative approach in descriptive method. Data analysis was performed by determining the dimensions of the textual and discours then newly implemented in the Indonesian language learning at school. This study obtained the result of (a) The framing in the main report of Tempo magazine has the news framing of the ideal in conveying fact based on the structure of syntax, script, thematic, and rhetorical tools as well as clear with the terms of the field of journalism. (b) The discouragement in the main report of Tempo magazine is a production process of the representation of events, characters, situations, actions, and social phenomena, as for the consumption process of interpretation views, ratings, and the interpretation of the reader. Then (c) the Implementation of research results in the learning can be applied in high School on the material to analyze and produce texts editorial/opinion, class XII (even) using the teaching of the Curriculum in 2013. Keywords: Tempo magazine, textual dimension, discourse dimension, and implementation